Stiff Extrusion Briquetting in Metallurgy - Kurunov, Ivan.; Bizhanov, Aitber; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book explains how the specifics of Stiff Extrusion influence on the metallurgical properties of Extruded Briquettes. The practical experience of the utilization of Stiff Extrusion in metallurgy obtained so far suggests that this technology can substitute (partially or by 100%) environmentally unfriendly sintering. The authors start reviewing the existing briquetting technologies, providing the reader later on with the specifics of stiff extrusion briquetting technology. Other aspects treated are the applications of extruded briquettes on blast furnace and for the production of manganese ferro alloys. The authors suggest stuff extrusion briquetting technology for direct reduction iron production and list several alternative unconventional applications.
Keywords: Metals; Manufactures; Pollution; Metals and Alloys; Machines, Tools, Processes; Pollution